Peran Guru dalam Mengelola Kelas Guna Meningkatkan Minat Belajar Siswa pada Mata Pembelajaran Pendidikan Pancasila di SD IT Ar-Raihan Pagar Alam - Yolanda, Anisa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research is motivated by the issues found at SD IT Ar-Raihan Pagaralam where students seem to lack interest in Pancasila Education. This can be observed through the students' attitudes during the teaching and learning process, such as not paying attention to the teacher during lessons, chatting with friends, feeling sleepy, and lacking enthusiasm in participating in the learning process. To address the students' low interest in learning, classroom management strategies are implemented. The objectives of this research are: 1) To describe the efforts of teachers in managing the classroom during Pancasila Education lessons at SD IT Ar-Raihan Pagaralam. 2) To describe the role of teachers in stimulating students' interest in learning Pancasila Education at SD IT Ar-Raihan Pagaralam. 3) To describe the role of teachers in managing the classroom to enhance students' interest in learning Pancasila Education at SD IT Ar-Raihan Pagaralam. This is a qualitative research with a descriptive analysis approach. The population of this study includes all 273 students at SD IT Ar-Raihan Pagaralam. The researcher used a non-probability sampling technique, selecting a sample of 30 students from grade V at SD IT Ar-Raihan Pagaralam. Data collection methods included observation, interviews, and documentation. The results indicate that teachers play various roles in teaching, such as learning facilitators, demonstrators, information sources, mediators, guides, facilitators, and motivators. However, these roles are not fully optimized, as there are still weaknesses in implementation and students' interest in Pancasila Education has not significantly improved. Students still do not feel entirely happy and engaged in Pancasila Education. Common issues faced by students in the learning process include difficulty concentrating, lack of motivation, and memory retention challenges. In conclusion, students do not exhibit a comprehensive interest in learning. Keywords: Teacher Role, Classroom Management, Learning Interest, Pancasila Education.